Myodes rutilus - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
52. Northern Red-backed Vole Myodes rutilus French: Campagnol boréal / German: Polarrételmaus / Spanish: Topillo rojo septentrional Other common names: Red ole Taxonomy. Mus rutilus Pallas, 1779, center of Ob River delta, Siberia, Russia. In the past, M. rutilus was included in Evotomys or Clethrionomys; both generic names are junior synonyms of Mpyodes. Present and past hybridization was documented in zone of sympatry with M. glareolus and in parapatric zone with M. gapperi. A number of subspecies have been recognized on both sides of Beringia, and their validity has been questioned with traditional subspecific systematics. Molecular reconstructions retrieved three divergent allopatric lineages with zones of secondary contact between them. These lineages diverged more than 100,000 years ago. Beringian lineage encompasses all populations in North America, Kamchatka, Sakhalin, and Hokkaido. Remaining Palearctic populations are in two lineages, separated by the Yenisei River. Monotypic. Distribution. From N & E Fennoscandia E across N European Russia and Siberia to Kamchatka, Sakhalin, Hokkaido, some Beringian Is (Unimak and St. Lawrence), Alaska, and N Canada; in the N it follows Siberian rivers to reach the shores of the Arctic Ocean, and in the S the range embraces N Kazakhstan, N Mongolia, N China (Xinjiang, Inner Mongolia [= Nei Mongol], Heilongjiang, and Jilin), and N North Korea. Introduced to Bering and Medny Is, offshore Kamchatka. Descriptive notes. Head-body 85-123 mm,tail 21-50 mm; weight 14-5-50 g. Females have four pairs of nipples. The Northern Red-backed Vole is very similar to the Bank Vole (M. glareolus). Bright reddish-brown dorsal pelage is frequently and clearly demarcated from grayish flanks. Winter pelage is brighter and denser, with 18-9 mg of hair/cm? vs. 10-6 mg of hair/cm? in summer. Tail is distinctly bicolored, ¢.33% of head-body length (shorter than the Bank Vole’s), and densely covered with hair; it has a long pencil. Albinos and melanistic individuals have been captured in the ...